2018
DOI: 10.1371/journal.pone.0197998
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of syndemic health problems in patients seeking post-exposure prophylaxis for sexual exposures to HIV

Abstract: IntroductionThe standard clinical approach to non-occupational HIV post-exposure prophylaxis (nPEP) focuses on biomedical aspects of the intervention, but may overlook co-occurring or ‘syndemic’ psychosocial problems that reinforce future vulnerability to HIV. We therefore sought to determine the prevalence of syndemic health problems in a cohort of Ontario nPEP patients, and explored the relationship between syndemic burden and HIV risk.MethodsBetween 07/2013-08/2016, we distributed a self-administered questi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…To mitigate this bias, the first question of the survey was, "Are you answering this survey for the first time?". On the definition of our highrisk behavior outcomes, we used three different definitions that have been consistently used in other studies as well as in guidelines to define populations at substantial risk of HIV infection [14][15][16][62][63][64]. The use of the HIRI-MSM as the outcome in the regression model precluded the evaluation of stimulants use as a covariate as it is already included in the scale.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this bias, the first question of the survey was, "Are you answering this survey for the first time?". On the definition of our highrisk behavior outcomes, we used three different definitions that have been consistently used in other studies as well as in guidelines to define populations at substantial risk of HIV infection [14][15][16][62][63][64]. The use of the HIRI-MSM as the outcome in the regression model precluded the evaluation of stimulants use as a covariate as it is already included in the scale.…”
Section: Discussionmentioning
confidence: 99%
“…This could be important for PEP-experienced users. A recent study in Toronto recorded a high prevalence of syndemic health problems among MSM seeking nPEP [28]. This clustering of syndemic conditions could partly explain low persistence on PrEP of nPEP users, which was also observed in other cohorts [29].…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, Storholm et al (2016) found an interaction effect between depression and sexual compulsivity, such that sexual compulsivity's effects on sexual behavior was moderated by depression. In contrast, Morrison et al (2018) did not detect interaction effects, which they interpreted to support the additive syndemics model. Tomori et al (2018) found only one significant two-way interaction when testing 2-and 3-way interactions among five syndemic conditions associated with CAS among MSM in India.…”
Section: Discussionmentioning
confidence: 82%